2004
DOI: 10.1029/2003jc001973
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of the global semidiurnal tide in the present day and in the last glacial maximum

Abstract: [1] A hydrodynamic model incorporating a self-consistent treatment of ocean selfattraction and loading (SAL), and a physically based parameterization of internal tide (IT) drag, is used to assess how accurately barotropic tides can be modeled without benefit of data, and to explore tidal energetics in the last glacial maximum (LGM). M 2 solutions computed at high resolution with present day bathymetry agree with estimates of elevations from satellite altimetry within 5 cm RMS in the open ocean. This accuracy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
407
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(437 citation statements)
references
References 41 publications
27
407
3
Order By: Relevance
“…The loss of shallow shelf seas during the LGM has likely led to increased tidal energy dissipation in the deep ocean, which in turn may have caused enhanced vertical mixing (20,21). On the other hand, the increased deep ocean stratification during the LGM may have suppressed vertical mixing, as more turbulent kinetic energy dissipation would be required to mix the more stratified water column (22).…”
Section: Sensitivity Experimentsmentioning
confidence: 99%
“…The loss of shallow shelf seas during the LGM has likely led to increased tidal energy dissipation in the deep ocean, which in turn may have caused enhanced vertical mixing (20,21). On the other hand, the increased deep ocean stratification during the LGM may have suppressed vertical mixing, as more turbulent kinetic energy dissipation would be required to mix the more stratified water column (22).…”
Section: Sensitivity Experimentsmentioning
confidence: 99%
“…Based on the observation that mixing rates over rough topography are enhanced (Polzin et al 1997;Ledwell et al 2000) and inverse models of the tides that suggested enhanced energy loss from the barotropic tides over rough topography (Egbert and Ray 2000), Jayne and St. Laurent (2001) applied a parameterization for topographic drag in a model of the barotropic tides and found that it improved the simulated tides. This parameterization represents the physics of the conversion of tidal energy into internal wave energy and is similar to the topographic drag parameterization used in atmospheric models (Palmer et al 1986;McFarlane 1987).…”
mentioning
confidence: 99%
“…Changes in sea level [e.g. likely altered the amount of tidal mixing, and in particular how tidal dissipation was partitioned between the continental shelves and the deep ocean [Egbert et al, 2004;Wunsch, 2005]. The degree to which changes in sea level may have changed the mixing within the ITF is unknown.…”
Section: Discussionmentioning
confidence: 99%